2015
DOI: 10.1007/s11136-015-1072-x
|View full text |Cite
|
Sign up to set email alerts
|

Normative data and psychometric properties of the Connor–Davidson Resilience Scale (CD-RISC) and the abbreviated version (CD-RISC2) among the general population in Hong Kong

Abstract: The Chinese version of the CD-RISC2 was demonstrated to be a reliable and valid measure in assessing resilience among the general population in Hong Kong.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 22 publications
6
62
4
1
Order By: Relevance
“…According to the CD-RISC2, the sample population analyzed here reported a resilience score of 5.6 ± 1.89. This score is lower than the 6.91 score reported in a general population survey of US adults [42], is close to the score of 5.85 ± 1.1 reported by Jeong et al in a Korean study, and is higher than that observed (5.03 ± 1.37) by Ni et al among the general population in Hong Kong [50,51]. Given the diversity of these societies in a global perspective, cultural factors and contexts may account for the differences in resilience score reported above.…”
Section: Discussionsupporting
confidence: 64%
“…According to the CD-RISC2, the sample population analyzed here reported a resilience score of 5.6 ± 1.89. This score is lower than the 6.91 score reported in a general population survey of US adults [42], is close to the score of 5.85 ± 1.1 reported by Jeong et al in a Korean study, and is higher than that observed (5.03 ± 1.37) by Ni et al among the general population in Hong Kong [50,51]. Given the diversity of these societies in a global perspective, cultural factors and contexts may account for the differences in resilience score reported above.…”
Section: Discussionsupporting
confidence: 64%
“…The CD‐RISC questionnaire mean result of 60.08 ± 13.90 (standard deviation) was well below the US standard average of 82 (Connor & Davidson, ); however, the data mirrored the Hong Kong general population and this might reflect a wider cultural aspect to the result (Table ) (Ni et al, ). The Cronbach's alpha of the CD‐RISC questionnaire results indicate that the questionnaire answers were extremely consistent (α = .940).…”
Section: Resultsmentioning
confidence: 81%
“…As illustrated in the CD‐RISC scale, the median score fell below both median CF scores from the USA. The results indicate either a need to establish a normative median value for this population or that this population is experiencing lower levels of resilience to CF when compared with the general population from the USA and Hong Kong (Ni et al, ). This study had the potential for errors in resilience assessment based on cultural settings.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…CD-RISC-10 was used as an anchor in this study. Cronbach's αs of 0.83, 0.79, and 0.85 are identi ed for CD-RISC-25, CD-RISC-2, and CD-RISC-10, respectively [18][19].…”
Section: Cd-riscmentioning
confidence: 99%